Internalisasi Nilai-Nilai Spiritual dalam Kepemimpinan Profetik di Madrasah - Balgies, Soffy; Tolchah, Moch; Amalia, Ainna (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2023)
This article presents research findings on the implementation of spiritual leadership in madrasas. The study used a qualitative method with a phenomenological approach. Data collection techniques included online surveys, interviews, and focus group discussions. The informant was the head of a public madrasa in Surabaya. The head of the madrasa contains Islamic values that are exemplified from the nature of prophetic leadership. This includes Siddiq, Amanah, Fatonah, and Tabligh, as well as awareness, commitment, cooperation, coolness, confidence, and discipline. The vision and mission are described in this way. The madrasah principal's leadership principles influenced the psychology of workers. This resulted in teachers and employees taking responsibility, helping each other, improving services, working sincerely, increasing self-capacity, and advancing student achievement. Finally, spiritual leadership impacts organizational behavior by creating a collaborative work culture that facilitates success and achievement for madrasas and students.